Bridging the Cultural Gap : A Case Study of a Church in Nepal - Kirchheiner, Ole (Book collections on Project MUSE., 2019)
This is an abridged version of Ole Kirchheiner's Regnum book, Culture and Christianity Negotiated in Hindu Society. Through an examination of the Nepali church the study pays special attention to the way ordinary Christians have been able to settle social and religious issues to live and work together with the traditional religious people of Nepal, and maintain a good family life.